\(x^3+4x^2+4x-16y^2\)
\(=\left(x^3+2x^2\right)+\left(2x^2+4x\right)-16y^2\)
\(=x^2.\left(x+2\right)+2x.\left(x+2\right)-16y^2\)
\(=\left(x+2\right).\left(x^2+2x\right)-16y^2\)
\(=x.\left(x+2\right).\left(x+2\right)-\left(4y\right)^2\)
\(=x.\left(x+2\right)^2-\left(4y\right)^2\)
\(=\left[\sqrt{x}.\left(x+2\right)\right]^2-4y^2\)
\(=\left[\sqrt{x}.\left(x+2\right)-4y\right].\left[\sqrt{x}.\left(x+2\right)+4y\right]\)
Tham khảo nhé~
nếu đưa vô căn phải có điều kiện là x > 0
\(x^3+4x^2+4x-16y^2=x\left(x+2\right)^2-\left(4y\right)^2\)
\(=\left(x\sqrt{x}+2\sqrt{x}\right)^2-\left(4y\right)^2=\left(x\sqrt{x}+2\sqrt{x}-4y\right)\left(x\sqrt{x}+2\sqrt{x}+4y\right)\)